PENDIDIKAN MULTIKULTURAL (Telaah Terhadap Sistem Pendidikan Nasional dan Pendidikan Agama Islam) - Asmuri Asmuri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
Indonesia is a country which has pluralistic varieties. The varieties can be viewed from two perspectives namely horizontal perspective and vertical perspective. The horizontal perspective covers the varieties of religions, ethnics, local languages, cloth, food and culture. Meanwhile, the vertical perspectives are included as the varieties of level of education, economic, shelters, jobs and the varieties of social – cultural. The varieties of our nation leads us the take into account the importance of multicultural education as an anticipation to the negative social phenomena which possibly derives from the varieties of races and tribes, religions, and varieties of values which exist in the society. The multicultural education can be implemented through learning models substantially by admitting and honoring the cultural diversities.